Elevations in Serum Creatinine With Tenofovir-Based HIV Pre-Exposure Prophylaxis: A Meta-Analysis of Randomized Placebo-Controlled Trials. (1st April 2016) - Yacoub, Rabi; Nadkarni, Girish N.; Weikum, Damian; Konstantinidis, Ioannis; Boueilh, Anna; Grant, Robert M.; Mugwanya, Kenneth K.; Baeten, Jared M.; Wyatt, Christina M.
Abstract : Supplemental Digital Content is Available in the Text.